Diesel-Sprayverhalten und Flamme-Wand-Interaktion bei hohen Temperaturen und Drücken - Held, Frank; Wensing, Michael (10. Symposium Trends in der Motorentechnologie, 2012)

Experimentelle Untersuchung des Diesel-Sprayverhaltens und der Flamme-Wand-Interaktion unter hohen Temperaturen und Drücken - Held, Frank (Friedrich-Alexander-Universität Erlangen-Nürnberg, 2015)
Im Rahmen der vorliegenden Arbeit werden Untersuchungen der Spray-Wand- und der Flamme-Wand-Interaktion unter dieselmotorischen Randbedingen präsentiert. Zudem wird eine neue Messtechnik zur Erfassung von Oberflächentemperaturen in Brennräumen vorgestellt. Die Interaktion von flüssigem sowie verbrennendem Kraftstoff mit den Brennraumwänden sind wichtige Aspekte innermotorischer Abläufe. Deshalb werden von einem definierten Referenzbetriebspunkt ausgehend verschiedene Parameter, wie zum Beispiel die Wandtemperatur, der Wandabstand sowie die Bedingungen in der Einspritzkammer, variiert. Die Messungen werden in einer Hochdruck-Hochtemperatur-Einspritzkammer mittels verschiedener optischer Messtechniken durchgeführt.Dabei ist zu beobachten, dass Erhöhungen der Wandtemperatur sich nicht immer positiv auf die Umsetzung des Kraftstoffs auswirken. Ab einer bestimmten Wandtemperatur wird der Zündverzug zu kurz, dies führt zu stark rußender Verbrennung. Weiterhin wird durch den Einsatz von Highspeed-Pyrometern und Thermoelementen der Wärmeübergang zwischen Dieselkraftstoff und der Wand charakterisiert. Entgegen der aus Literatur bekannten Messungen, wird unter den untersuchten Bedingungen ein Wärmeübergang vom Dieselspray in die Wand ermittelt. Darüber hinaus wird eine neue Messtechnik zur minimal invasiven Erfassung von Brennraumwandtemperaturen vorgestellt. Diese Messstrategie ist grundsätzlich zur Ermittlung von Brennraumoberflächentemperaturen in allen Energiewandlern geeignet, die mit einem optischen Zugang, beispielsweise einem Endoskop, ausgerüstet werden können. Die Funktionstüchtigkeit dieser Technik wird mit verschiedenen Testmessungen in einem Diesel-Transparentmotor belegt.<br
Keywords: Diesel; Wandinteraktion; Sprühen

Kraftstoffeinflüsse auf den Dieselmotorischen Prozessablauf - Kühling, K.; Kleine Jäger, F.; Wensing, Michael; Schmid, M.; Held, Frank (Motorische Verbrennung – aktuelle Probleme und moderne Lösungsansätze, 2009)

Time and Spatially Resolved Measurements of the Interaction between Liquid and Combusting Diesel Spray and Walls in Modern Diesel Engine Conditions - Held, Frank; Bornschlegel, Sebastian; Rieß, Sebastian; Vogel, Thomas; Wensing, Michael (2013)
Spray- and flame-wall interactions were investigated in a combustion chamber with diesel engine conditions. Several techniques were used to perform time and spatially resolved measurements of the liquid fuel phase, the premixed and diffusion-controlled combustion close to a wall. Different wall and gas temperature variations were investigated. It was found that low temperature variations of 25 K have a significant impact on the combustion process: The lower the gas temperatures, the more liquid fuel and larger vortex structures arise. Also, the ignition delay is elongated. Consequently, the premixing period is longer, which can lead to the complete disappearance of sooty combustion. The colder the wall, larger cooling of the spray and larger vortex structures of liquid fuel on the wall develop. The ignition delays again are noticeable longer at the colder wall. Therefore, the premixing period is longer and there is also much less sooty combustion when the wall temperature is lower. Further, a reference fuel following the European normative EN 590 (CEC) and a rapeseed fuel (RME) were compared. The ignition delay of CEC is shorter than that of RME. This is remarkable, since measurements without wall interaction showed the opposite. It is important for the spray-wall- interaction whether the fuel is liquid or vaporized when the interaction takes place, because of an intensified heat exchange in the case of liquid wall interaction.<br

Time and Spatially Resolved Measurements of the Interaction of Combusting Diesel Spray and Walls with Elevated Temperatures - Held, Frank; Vogel, Thomas; Wensing, Michael; Werblinski, Thomas (SAE International Journal of Engines, 2012)
The interaction between a combusting diesel spray and a wall at temperatures of 700K and 735K was investigated in a combustion chamber using optical measurement techniques. The temperatures were chosen as they appear in the range of the maximum piston surface temperatures of the latest production engines. Combustion was investigated with a dual camera setup, which is designed to take simultaneous pictures of the UV flame luminosity (FL_UV) and the visible flame luminosity (FL_VIS). The FL_UV is used to measure lean or stoichiometric combustion. The FL_VIS is capable of detecting the thermally excited soot. Mie scattering is used to study the liquid fuel phase. It was found that there is almost no FL_VIS signal visual in the 700K case, but a very strong signal in the 735K case. In general, one might expect that higher wall temperatures lead to an improved mixture formation and, consequently, lower soot production. However, the opposite was detected. The reason for this is that the ignition delay is much larger at the colder wall and, therefore there is more time for premixing. Also the FL_OH signal is much weaker at the lower wall temperature. This can be explained by the fact that the OH-radical is not only a marker of lean combustion, but also a marker of soot oxidation. In addition, the ignition delays are compared at different measurement settings. It can be assumed that the ignition delays are shorter in the hot wall cases and also shorter at the higher ambient gas pressures. The comparison between unaffected spray and wall-influenced spray shows that ignition delays for the unaffected spray cones are always smaller or equal to those for wall-influenced ignition. Moreover, the differences between ignition delays tend to be smaller at the higher wall temperatures.
Created from Fastlane, Scopus look-up

Untersuchung der Wechselwirkungen von flüssigem und verbrennendem Dieselkraftstoff mit Wänden unter hohen Temperaturen und Drücken - Held, Frank; Werblinski, Thomas; Vogel, Thomas; Wensing, Michael (Motorische Verbrennung- Aktuelle Probleme und moderne Lösungsansätze (XI. Tagung), 2013)